Knowledge Representations and Knowledge Transfer - Boland, Richard J.; Singh, Jagdip; Salipante, Paul F.; Aram, John D.; Fay, Sharon Y.; Kanawattanachai, Prasert (Academy of Management Journal, 2001)
Cognitive and learning theories were used to develop a framework in which different knowledge representations prime recipients with different schemata and thereby differentially affect their decision making. The authors evaluated interpretive, general, and particular knowledge representations in a laboratory experiment with managers. The hypotheses received mixed support, with significant results indicating the importance of particular knowledge representations in managerial decision making and an intriguing role for interpretive knowledge representations.